2016
DOI: 10.1177/1362361316655035
|View full text |Cite
|
Sign up to set email alerts
|

Examining the reinforcing value of stimuli within social and non-social contexts in children with and without high-functioning autism

Abstract: One of the key diagnostic criteria for autism spectrum disorder includes impairments in social interactions. This study compared the extent to which boys with high-functioning autism and typically developing boys “value” engaging in activities with a parent or alone. Two different assessments that can empirically determine the relative reinforcing value of social and non-social stimuli were employed: paired-choice preference assessments and progressive-ratio schedules. There were no significant differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Behavior analytic research seeking to identify and evaluate social behaviors and reinforcers indicates otherwise, however. Goldberg et al (2017) showed that children with ASD responded the same way as their typically developing peers when asked to choose between, or were required to work for, a solitary or social activity space. Furthermore, research with individuals with ASD has repeatedly shown that social interactions may function as a reinforcer for problem behavior (e.g., Piazza et al, 1999) and that individuals with ASD will differentially respond for more preferred social interactions (e.g., Kelly et al, 2014; Morris & Vollmer, 2019, 2020a, 2020b, 2020c).…”
mentioning
confidence: 99%
“…Behavior analytic research seeking to identify and evaluate social behaviors and reinforcers indicates otherwise, however. Goldberg et al (2017) showed that children with ASD responded the same way as their typically developing peers when asked to choose between, or were required to work for, a solitary or social activity space. Furthermore, research with individuals with ASD has repeatedly shown that social interactions may function as a reinforcer for problem behavior (e.g., Piazza et al, 1999) and that individuals with ASD will differentially respond for more preferred social interactions (e.g., Kelly et al, 2014; Morris & Vollmer, 2019, 2020a, 2020b, 2020c).…”
mentioning
confidence: 99%
“…In addition, the use of a progressive‐ratio analysis for evaluating relative reinforcement effects under increasing schedule requirements replicated previous research (e.g., Roane et al, ). Although other studies have evaluated single (Tustin, ) or general (Goldberg et al, ) social interactions under progressive‐ratio schedules, this is the first study to evaluate the efficacy of different types of social interactions under a progressive‐ratio schedule. Because all social interactions from the preference assessment array were included in the progressive‐ratio analysis in the current study, the validity of the preference hierarchy could be determined.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, if observers actually received what is represented by the preferred image (e.g., joining the interaction depicted in the image) then this would likely alter choice behavior. This is important in the context of a recent, novel study that indexed forced choices between actually engaging in (as opposed to simply observing) social and nonsocial activities, which found no difference between ASD and NT observers (Goldberg et al, 2017). By extension, it is important to acknowledge that the choice data presented here may be better described as reflecting responsivity to social rewards, rather than social motivation per se.…”
Section: Discussionmentioning
confidence: 99%